Determination of Tebing Keraton Recreation Demand Functions With Travel Cost Method - Deni Rusmaya; Astri Widiastuti Hasbiah; Tsabit Walad al Wahad (Journal of Community Based Environmental Engineering and Management, 2022)
Forest recreation services as additional products that are intangible. It can not be quantified because it does not have a price on the normal market system. It underlies a study to determine the economic value of recreation, with case studies Tebing Keraton using the Individual Travel Cost Method. Analysis of data obtained from questionnaires using data processing equipment SPSS version 21 with multiple linear regression method to get the Tebing Keraton recreation demand functions. The variables that influence the number of visits are travel cost, total income, age, mileage, and gender. Coefficient values of variables determine the trend in increasing or decreasing the number of tourist visits. In this study, the demand functions divided into two recreational functions for students/scholar and for working people considering total income per month category. Based on the regression results, demand functions for students/scholar, is Y=-2.179–0.0000347X1+0.286X2+0.159X3-0.0000794X4-0.267X5, and for working people is Y=1.994–0.00000164X1+0.53X2-0.32X3-0.003X4-0.334X5. The regression result obtained a coefficient of determination (R2) that the percentage of the diversity of demand number of visits to Tebing Keraton which can be explained by the independent variables in the model. R2 value of model for students/scholar is 67.1%, which is more than 0.5, showing the moderate accuracy. While for working people, the value of R2 is 48.9%, which is in the range of 0.31 – 0.5, indicate the weak accuracy.